(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the long-term outcomes of surgical treatment for congenital hip dislocation in children aged 1-6 years. Methods: Retrospective analysis of 164 patients (181 hips) treated between 2016 and 2020 with follow-up until 2025. Functional outcomes assessed by CHOHES. Results: 88.9% of hips underwent open reduction with femoral osteotomy and acetabular reconstruction. Redislocation occurred in 6.6%, avascular necrosis in 12.7%. At final follow-up, 88.1% had good to fair outcomes. Conclusion: One-stage open reduction with femoral and acetabular osteotomies offers effective long-term stability and function in children under 6 years.